Primary Sourcing: the Ten Thousand Rooms Platform for Digital Annotation of Primary Source Images. Issue 2 (July 2020) - Frisch, Nicholas
Abstract: The Ten Thousand Rooms Project offers a modern digital solution to an age-old scholarly problem: a platform for annotating source texts for easy reference and retrieval, while facilitating easy access to original sources. Individuals or groups can upload scans of primary sources and annotate over the image, in multiple layers, toggling annotations on or off per research and reading needs. The project is hosted by Yale University.